A Cd(ii)-based metal–organic framework as a luminance sensor to nitrobenzene and Tb(iii) ion. Issue 16 (17th March 2016) - Qu, Xiang-Long; Gui, Di; Zheng, Xiao-Li; Li, Rui; Han, Hong-Liang; Li, Xia; Li, Pei-Zhou
Abstract : A highly stable Cd(ii )-based metal–organic framework was successfully obtained. It shows a highly selective sensing effect not only towards organic pollution molecule, nitrobenzene, via a strong quenching effect, but also to an inorganic Tb(iii ) ion by a strong green emission effect. Abstract : A Cd(ii )-based metal–organic framework, [Cd2 (DPDC)2 (BTB)]∞ (Cd-MOF, DPDC = 2, 2′-diphenyldicarboxylate and BTB = 1, 4-bis(1, 2, 4-triazol-1-yl)butane) was successfully constructed via a hydrothermal reaction. Structural analysis shows that the synthesizedCd-MOF is a three-dimensional (3D) architecture crystallized in the hexagonal system with a chiral space group P 61 . Powder X-ray diffraction experiments and thermogravimetric analysis reveal that the constructedCd-MOF has a high chemical and thermal stability. A study of additional mechanical properties indicates that it exhibits a moderate stiffness with the average values of Young's modulus ( E ) and H as 11.3(2) and 0.9(7) GPa, respectively. The luminescence properties of theCd-MOF were further studied. The result shows that it could be an effective sensor to the organic nitrobenzene molecule via a strong quenching effect, and also to the inorganic Tb(iii ) ion by a strong green emission effect. Moreover, when loading bimetal ions (Eu(iii ) and Tb(iii )) into theCd-MOF /methanol suspension, tunable visible luminescence can also be achieved by carefully adjusting the excitation wavelengths.